Organizational commitment level of teaching staff in the health sector- Tishreen University and factors affecting it - Taweel, Alaa Mahmoud (Latakia University Journal -Medical Sciences Series, 2020)
The study aimed to determine the level of teaching staff ‘s organizational commitment of the health sector in Tishreen University and identify the factors affecting it. The sample consisted of (120) members of the teaching staff of the health sector colleges in Tishreen University (medicine, dentistry, pharmacy, nursing) who were presented during the data collection and agreed to participate in the study (convenience sample). The researcher used the questionnaire of organizational commitment consisting of (38) items according to four dimensions: the loyalty of the job dimension, the responsibility towards the university dimension, the desire to continue the work dimension, and faith in the university dimension, The Likret triangular scale was used, and the factors influencing their organizational commitment from 1-10 were arranged. After the data collection, the data were released and analyzed using (SPSS version 20). The most important results of the research were: The level of organizational commitment of teaching staff working in the health sector at the university was generally high. The factors influencing the organizational commitment of teaching staff (the sample of the research) were as arranged by them: the incentive system at the university, and the level of salary that the member receives from the university, the good relationship between colleagues at the university, then the organizational climate at the university…, the tenth and last rank included the clarity of the job functions and the work procedures for the job at the university(job description). There was no statistically significant relationship between the level of organizational commitment of teaching staff and their demographic data (college, career level, gender, age, years of experience or service at the university). هدف البحث إلى تحديد مستوى الالتزام الوظيفي لأعضاء الهيئة التعليمية للقطاع الصحي في جامعة تشرين وتحديد العوامل المؤثرة فيه. تكونت العينة من(120) عضو هيئة تعليمية من العاملين في كليات القطاع الصحي في جامعة تشرين (طب بشري, طب الأسنان, صيدلة, تمريض) , ممن حضروا أثناء جمع البيانات ووافقوا على المشاركة في الدراسة (العينة المتاحة). استخدم الباحث أداة (استبانة) الالتزام التنظيمي المكون من (38) عبارة وفق أربعة أبعاد: بُعد الولاء الوظيفي, بُعد المسؤولية تجاه الجامعة, بُعد الرغبة في الاستمرار بالعمل, و بُعد الإيمان بالجامعة, واستخدم مقياس ليكرت الثلاثي, كما قام أفراد العينة بترتيب العوامل المؤثرة في التزامهم التنظيمي من 1-10. وبعد جمع البيانات, تم تفريغ البيانات و تحليلها باستخدام أساليب و برامج إحصائية متخصصة (SPSS النسخة 20). أهم النتائج التي توصل إليها البحث: أن مستوى الالتزام التنظيمي لدى أعضاء الهيئة التعليمية العاملين في القطاع الصحي في الجامعة كان مرتفعاً بشكل عام. العوامل المؤثرة على الالتزام التنظيمي لأعضاء الهيئة التعليمية (عينة البحث) كانت كما رتبها أعضاء الهيئة التعليمية : نظام الحوافز في الجامعة, ثم مستوى الراتب الذي يتقاضاه العضو من الجامعة, فالعلاقة الطيبة بين الزملاء في الجامعة, ثم المناخ التنظيمي في الجامعة, ..., وجاء في المرتبة العاشرة والأخيرة وضوح المهام الوظيفية وإجراءات العمل الخاصة بالوظيفة في الجامعة (التوصيف الوظيفي). لم توجد علاقة ذات دلالة احصائية بين مستوى الالتزام التنظيمي لأعضاء الهيئة التعليمية والبيانات الديموغرافية الخاصة بهم (الكلية, المستوى الوظيفي, الجنس, العمر, وسنوات الخبرة أو الخدمة في الجامعة).